Identification and prioritization of barriers to total quality management implementation in service industry: An analytic hierarchy process approach. Issue 5 (10th August 2015) - Talib, Faisal; Rahman, Zillur
Abstract : Purpose: – Despite the potential benefits of total quality management (TQM) articulated by quality experts and practitioners, these benefits are not easy to achieve in practice. Many service industries have found difficult to implement TQM successfully. The present study investigates and categorizes the barriers to a successful implementation of TQM program in the service industry. The purpose of this paper is to understand TQM barriers and prioritize their relative importance by ranking them in the service industry. Design/methodology/approach: – Based on previously published literature on TQM barriers in service industry and after discussions with quality experts, this study utilizes a set of 12 barriers to TQM as identified by the authors of TQM barriers to accomplish the objectives of the present study. The 12 barriers were divided into three categories. These barriers were prioritized and ranked using an analytic hierarchy process (AHP) approach, a multi-criteria decision-making process. Findings: – In this research, the category "managerial issues" was found to be the most important, followed by "people-oriented issues" and "organizational issues" based on their priority weights. The results have also highlighted that the barrier "lack of communication" was the most significant among all the other barriers. It was followed by "lack of top-management commitment, " "employee's resistance to change, " and "lack of coordination between departments." The least significant barrier was "high turnover at management level." Practical implications: – The study ranks the barriers, from the most important to the least important, which will allow managers and practitioners in the service industry to decide which barriers they need to pay attention to and work on for a successful implementation of TQM. Originality/value: – The strength of this study is the development of a comprehensive model for the investigation and prioritization of barriers that the service industry experiences when implementing a TQM program. Presenting TQM barriers in the form of AHP-based model and categorizing barriers is a new effort in the area of TQM.